Finding Grace and Hope in Community - Kirkpatrick, Martha (Maine Policy Review, 2008)
Martha Kirkpatrick urges readers to focus on sense of community in facing the challenges of scarce energy and fuel sources, unstable prices, and the increasing environmental havoc brought about by human activity. She reminds readers that Mainers are resilient and resourceful, and that a strong sense of community remains in many places that should be nurtured and supported by state government.